Forage production and interspecific competition of oats (Avena sativa) and common vetch (Vicia sativa) association under dry land and high-altitude conditions - Espinoza-Montes, Francisco (2018)
The oats (Avena sativa) and common vetch (Vicia sativa) cultivated in association was evaluated under dry land conditions at 4035 m above sea level to determine its performance and effects on yield, forage quality and interspecific competition. On average, the yield of green forage, dry matter and quality of forage were higher than that of oat monoculture (p1). None of the species showed aggressive behaviour (A=0) and greater competitive ability of the common vetch (CR>1) was observed compared with the competitive capacity of oats.